From Commodity Discovery to Production - Khan, Tehmina (World Bank, Washington, DC, 2016)
Major resource discoveries have transformed growth prospects for many low-income countries. However, the sharp downturn in commodity prices in recent years is affecting resource investment in these countries, and may delay the development of recent discoveries into production. This study investigates lead times from discovery to production for a unique data set of gold and copper discoveries worldwide during 1950-2014. The study employs standard parametric and nonparametric duration analysis. The results suggest an important role for copper prices; for instance, an upswing at the time of discovery can hasten the development of the mine by two to three years in low-income countries. There appears to be a similarly beneficial impact on lead times of sounder macroeconomic policies and quality of governance.